Strategi Abdullah Said Dalam Mewujudkan Mimpi Besarnya Dalam Mencetak Agen Perubahan Sosial - Muhammad Zarly Haqiqi; Adi Haironi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This study aims to examine the strategy of Da'wah and cadre applied by Kh Abdullah Said in forming agents of social change in Indonesia. The background of this study is the significant role of Abdullah Said in the world of Da'wah and Islamic education through the establishment of Hidayatullah Islamic boarding school. The research method used is a literature study, where data is collected from various library sources such as books, journals, and related documents. Research findings indicate that Abdullah Said placed da'wah as a top priority and was active in Cadre from a young age. He developed a structured method of Da'wah known as Manhaj Sistematika Nuzulul Wahyu, and founded a boarding school that combined religious education with practical skills training. The implications of this study suggest that a systematic approach and high commitment in Da'wah can produce effective agents of social change. The study also suggests the need for further research to explore the long-term impact of Abdullah Said's da'wah methods in different social contexts.